Lion Island : Cuba's warrior of words - Engle, Margarita (Atheneum Books for Young Readers, 2017)
Antonio Chuffat, a young man of Chinese and African descent, works as a messenger for Chinese diplomats in Cuba during the 1870s. Surrounded by African slaves and indentured Chinese servants, Antonio meets a boy named Wing and his sister Fan, both refugees who fled San Francisco during the anti-Chinese riots. The three become determined to fight for freedom. But while Antonio prefers to use words, Wing would rather use force.